2020
DOI: 10.1186/s12891-020-03458-0
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of FTX promotes the differentiation of osteoclasts in osteoporosis through the Notch1 signaling pathway by targeting miR-137

Abstract: Background: Osteoporosis (OP) is one of the commonly seen bone diseases with low bone mineral densities and trauma fractures. Accumulative studies have demonstrated that the occurrence of OP is closely related to osteoclasts differentiation. LncRNA FTX has been demonstrated to inhibit the development of some human cancers. However, its potential functions in human OP remains to be elusive. Methods: The expressions of FTX and miR-137 in bone and serum samples of patients with or without OP were measured. Bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…AC005261.1 is antisense to a KRAB-containing zinc finger transcription gene ZNF304 , which plays a fundamental role in T-cell differentiation (Sabater et al, 2002). FTX, an X-inactive-specific transcript regulator, previously was demonstrated to have a regulatory function in cell proliferation of multiple tumor types (Huang et al, 2020), and its down-regulation promotes the differentiation of osteoclasts in osteoporosis (Yu et al, 2020b). Taken together, these results demonstrate that dynamic expression of lncRNA genes is an integral component of the transcriptional profiles of osteogenic differentiation and may contribute to the regulation of osteogenic differentiation by regulating proximal coding genes.…”
Section: Resultsmentioning
confidence: 99%
“…AC005261.1 is antisense to a KRAB-containing zinc finger transcription gene ZNF304 , which plays a fundamental role in T-cell differentiation (Sabater et al, 2002). FTX, an X-inactive-specific transcript regulator, previously was demonstrated to have a regulatory function in cell proliferation of multiple tumor types (Huang et al, 2020), and its down-regulation promotes the differentiation of osteoclasts in osteoporosis (Yu et al, 2020b). Taken together, these results demonstrate that dynamic expression of lncRNA genes is an integral component of the transcriptional profiles of osteogenic differentiation and may contribute to the regulation of osteogenic differentiation by regulating proximal coding genes.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (17%) recruited younger participants in healthy control groups [ 38 , 41 , 42 , 44 , 47 , 59 , 60 , 71 , 78 ] and did not match for age, causing potential selection bias. Almost all the studies considered female osteoporotic and sarcopenic patients (76%), but 14/59 studies also included male patients [ 34 , 38 , 50 , 52 , 53 , 58 , 59 , 60 , 61 , 62 , 66 , 73 , 77 , 82 , 83 ]. Twelve studies on osteoporosis and two on sarcopenia did not state sex.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-137 has been reported to participate in the progression of various cancers ( Li et al , 2017 ; Liu et al , 2017; Qin et al , 2017 ; Luo et al , 2018 ; Zhang et al , 2018 ), development and maturation of neurons ( Silber et al , 2008 ; Szulwach et al , 2010 ; Tarantino et al , 2010 ; Sun et al , 2011 ; Jiang et al , 2013 ) and bone metabolism ( Zheng et al ,2019 ; Kong et al , 2020 ; Ma et al , 2020 ; Yu et al , 2020 ; Fan et al , 2021 ). But compared with the previous two research fields, miR-137-modulated osteogenic differentiation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miR-137 acts as a key regulator in various kinds of malignancies ( Li et al , 2017 ; Liu et al , 2017 ; Qin et al , 2017 ; Luo et al , 2018 ; Zhang et al , 2018 ) and neural development ( Silber et al , 2008 ; Szulwach et al , 2010 ; Tarantino et al , 2010 ; Sun et al , 2011 ; Jiang et al ,2013 ). But up to present, only a few studies investigated the effects of miR-137 on osteogenesis ( Zheng et al , 2019 ; Kong et al , 2020 ; Ma et al , 2020 ; Yu et al , 2020 ; Fan et al , 2021 ), and the mechanisms of osteogenic modulation by miR-137 are still not fully understood, especially considering the diverse biological properties of different cell types.…”
Section: Introductionmentioning
confidence: 99%